Effectiveness of a targeted exercise intervention in reversing older peoples mild balance dysfunction: A randomised controlled trail - Xiao, J.; Hill, Keith; Moore, K.; Williams, S.; Dowson, L.; Borschmann, K.; Simpson, J.; Dharmage, S. (American Physical Therapy Association, 2012)
Background: Previous research has mainly targeted older people with high risk of falling. The effectiveness of exercise interventions in older people with mild levels of balance dysfunction remains unexplored. Objective: This study evaluated the effectiveness of a home balance and strength exercise intervention in older people systematically screened as having mild balance dysfunction. Design: This was a community-based, randomized controlled trial with assessors blinded to group allocation. Participants: Study participants were older people who reported concerns about their balance but remained community ambulant (n=225). After a comprehensive balance assessment, those classified as having mild balance dysfunction (n=165) were randomized into the trial. Intervention: Participants in the intervention group (n=83) received a 6-month physical therapist–prescribed balance and strength home exercise program, based on the Otago Exercise Program and the Visual Health Information Balance and Vestibular Exercise Kit. Participants in the control group (n=82) continued with their usual activities. Outcome Measures: Laboratory and clinical measures of balance, mobility, and strength were assessed at baseline and at a 6-month reassessment.Results: After 6 months, the intervention group (n=59) significantly improved relative to the control group (n=62) for: the Functional Reach Test (mean difference=2.95 cm, 95% confidence interval [CI]=1.75 to 4.15), the Step Test (2.10 steps/15 seconds, 95% CI=1.17 to 3.02), hip abductor strength (0.02, 95% CI=0.01 to 0.03), and gait step width (2.17 cm, 95% CI=1.23 to 3.11). There were nonsignificant trends for improvement on most other measures. Fourteen participants in the intervention group (23.7%) achieved balance performance within the normative range following the exercise program, compared with 3 participants (4.8%) in the control group. Limitations: Loss to follow-up (26.6%) was slightly higher than in some similar studies but was unlikely to have biased the results. Conclusions: A physical therapist–prescribed home exercise program targeting balance and strength was effective in improving a number of balance and related outcomes in older people with mild balance impairment.